The Use of Crossword Puzzle Media in Fiqh Learning at Mts Nurus Syafi’i Gedangan Sidoarjo - Millatus Shofi (PT. Pusmedia Group Indonesia, 2025)
This study focuses on the use of Crossword Puzzle media in Fiqh learning at MTs Nurus Syafi’i Gedangan, Sidoarjo. The core issues examined include three essential aspects: the planning of the media’s implementation, the execution of its use within classroom instruction, and the evaluation conducted following its application. These three points were selected to provide a comprehensive understanding of how effective the Crossword Puzzle is as an activity-based instructional strategy.The research aims to explore in depth how teachers design the Crossword Puzzle media in alignment with existing instructional documents, how it is implemented within Fiqh learning activities, and how the evaluation outcomes reflect its influence on students. A qualitative approach was employed because it enables natural and holistic interpretation of classroom phenomena. Data were gathered through classroom observations, interviews with teachers and students, and documentation analysis, resulting in rich and descriptively presented findings.The results indicate that Fiqh learning at MTs Nurus Syafi’i is structured based on teaching modules standardized through MGMP, then adjusted to the specific needs and characteristics of the school and its learners. During instruction, the Crossword Puzzle is used to reinforce students’ understanding of Fiqh concepts while encouraging active participation. Learning activities proceed through structured steps in which the crossword serves as a concept-reinforcement tool. Evaluation findings reveal positive student responses, with many acknowledging that the media enhanced their comprehension. Minor shortcomings were identified, mainly related to differences in student abilities when completing the crossword. However, these variations are considered normal, as they reflect the diversity of learners’ characteristics and learning paces.